Disinfection:A View from the Early 21st Century - Bal, C; Hoffman, PN; Rotter, ML (International Journal of Infection Control, 2009)
The origins of today’s disinfection practices go back to the 19th century. Although we have learned much since then, there are still gaps in our knowledge; gaps both in theory and in the practical application of disinfection. This collection of three short papers is taken from a session at the 6th Congress of the International Federation of Infection Control held in Istanbul, Turkey in October 2005. It provides an overview of the current status of disinfection, as well as an assessment of possible problems yet to come.